Study protocol for the road to hierarchical diabetes management at primary care (ROADMAP) study in China: a cluster randomised controlled trial - Puhong Zhang; Xian Li; Yuqian Bao; Weiping Jia; Nadila Duolikun; Dalong Zhu (BMJ Open)
Introduction Diabetes management in primary care remains suboptimal in China, despite its inclusion in the essential public health service (EPHS). We aimed to evaluate the effectiveness of a mobile health (mHealth) based and three-tiered diabetes management system in diverse Chinese contexts.Methods and analysis This is a cluster randomised controlled trial, named road to hierarchical diabetes management at primary care (ROADMAP). 19 008 patients with type 2 diabetes (T2D) were recruited from primary care clinics in 864 communities across 144 counties/districts of 24 provinces. Eligible participants were adult patients diagnosed with T2D and registered for diabetes management in communities. Patients within the same communities (clusters) were randomly allocated into the intervention or control arm for 1 year in a 2:1 ratio. The control arm patients received usual care as EPHS packaged: at least four blood glucose (BG) and blood pressure (BP) tests, and lifestyle and medication instruction, yearly, from primary care providers. The intervention arm patients received at least two BG and one BP tests, monthly, and lifestyle and treatment instruction from a three-tiered contracted team. A mHealth platform, Graded ROADMAP, enabled test results uploading and sharing, and patient referral within the team. The intervention participants will be further divided into basic or intensive intervention group according to whether they were actively using the Your Doctor App. The primary outcome is the BG control rate with glycated haemoglobin (HbA1c)<7.0%. Secondary outcomes include control rates and changes of ABC (HbA1c, BP and low-density lipoprotein cholesterol) and fasting BG, hypoglycaemia episodes and health-related quality of life (EuroQol (EQ-5D)).Ethics and dissemination The trial has been approved by the Institutional Review Board at Shanghai Sixth People's Hospital. Findings on the intervention effectiveness will be disseminated through peer-reviewed journals, conference presentations and other relevant mechanisms.Trial registration number ChiCTR-IOC-17011325.